CD4 T Cell Count in Newly diagnosed PTB Patients With Reference to their HIV Sero status - Rajbhandari, Piyush; Bhattacharya, Shyamal Kumar; Gurung, Rajendra; Poudyal, Nimesh; Pradhan, Bickram (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: CD4 and CD8 T cells facilitate the containment of tuberculosis (TB) and has been postulated that there will be changes in their level in patients with TB. This study was carried out to analyze the CD4 cell counts in pulmonary tuberculosis (PTB) patients with reference to their HIV status. Methods: A cross-sectional study was conducted at the Department of Microbiology of a tertiary care hospital of eastern Nepal from May 2012 to April 2013. A total of 160 individuals, 40 each in the PTB, PTB/HIV, HIV and healthy population were included after obtaining informed consent. PTB and HIV diagnosis was made according to national guidelines. CD4 T cells were analyzed using a BD FACS Count Cytometer. Data were entered in Microsoft Excel 2007 and analyzed using SPSS version 11.7. Results: The mean absolute CD4 cells in PTB patient were 562.20 ± 197.3 cells/ul, which was a clear reduction (p < 0.001) when compared to the healthy population of this area (786.30 ± 239.17 cells/ul). There was significant decrease in the CD4 level among the HIV/TB patient (123.70 ± 99.4 cells/ul) as compared to PTB patient without HIV (p < 0.001). The study also noted that the mean CD4 cell level among HIV infected population (249.68 cells/ul) was higher compared to the HIV/TB co-infected population (p < 0.05). Conclusion: CD4 cell count can reflect the degree of immunosuppression in PTB patient irrespective of their HIV status but it cannot predict the disease severity in PTB patient.